Comparison of Fitness Cost and Virulence in Chromosome- and Plasmid-Mediated Colistin-Resistant Escherichia coli - Choi, Yujin; Lee, Ji-Young; Lee, Haejeong; Park, Myungseo; Kang, KyeongJin; Lim, Suk-Kyung; Shin, Dongwoo; Ko, Kwan Soo (Frontiers in Microbiology, 2020)
Five types of Escherichia coli strains were obtained and sequenced: colistin-susceptible (CL-S) strains, in vitro induced colistin-resistant (CL-IR) strains, mcr-1-negative colistin-resistant strains from livestock (CL-chrR), mcr-1-positive colistin-resistant strains (CL-mcrR), and mcr-1-transferred transconjugants (TC-mcr). Amino acid alterations of PmrAB, PhoPQ, and EptA were identified, and their mRNA expression was measured. Their growth rate was evaluated, and an in vitro competition assay was performed. Virulence was compared through serum resistance and survival in macrophages and Drosophila melanogaster. CL-IR and CL-chrR strains were colistin-resistant due to amino acid alterations in PmrAB, PhoPQ, or EptA, and their overexpression. All colistin-resistant strains did not show reduced growth rates compared with CL-S strains. CL-IR and CL-chrR strains were less competitive than the susceptible strain, but CL-mcrR strains were not. In addition, TC-mcr strains were also significantly more competitive than their respective parental susceptible strain. CL-IR strains had similar or decreased survival rates in human serum, macrophages, and fruit flies, compared with their parental, susceptible strains. CL-chrR strains were also less virulent than CL-S strains. Although CL-mcrR strains showed similar survival rates in human serum and fruit fly to CL-S strains, the survival rates of TC-mcr strains decreased significantly in human serum, macrophages, and fruit flies, compared with their susceptible recipient strain (J53). Chromosome-mediated, colistin-resistant E. coli strains have a fitness cost, but plasmids bearing mcr-1 do not increase the fitness burden of E. coli. Along with high usage of polymyxins, no fitness cost of mcr-1-positive strains may facilitate rapid spread of colistin resistance.